Microsaccade-induced prolongation of saccade latencies depends on microsaccade amplitude (Journal of Eye Movement Research, 2008)
Fixations consist of small movements including microsaccades, i.e., rapid flicks in eye position that replace the retinal image by up to 1 degree of visual angle. Recently, we showed in a delayed-saccade task (1) that the rate of microsaccades decreased in the course of saccade preparation and (2) that microsaccades occurring around the time of a go signal were associated with prolonged saccade latencies (Rolfs et al., 2006). A re-analysis of the same data set revealed a strong dependence of these findings on microsaccade amplitude. First, microsaccade amplitude dropped to a minimum just before the generation of a saccade. Second, the delay of response saccades was a function of microsaccade amplitude: Microsaccades with larger amplitudes were followed by longer response latencies. These finding were predicted by a recently proposed model that attributes microsaccade generation to fixation-related activity in a saccadic motor map that is in competition with the generation of large saccades (Rolfs et al., 2008). We propose, therefore, that microsaccade statistics provide a behavioral correlate of fixation-related activity in the oculomotor system.